Sex Differences in Group Composition and Habitat Use of Iberian Free-Range Pigs - Dalmau, Antoni; Martínez-Macipe, Míriam; Manteca, Xavier; Mainau, Eva (Frontiers in Veterinary Science, 2020)
The aim of the present work was to study group size, group composition and habitat use of Iberian pigs along the year when reared outdoor. This consists of a regimen in which animals are reared free range from two months of age until at least 14 months of age. In a first stage, animals are supplemented with concentrates, and in a second, called montanera, pigs eat just natural resources in areas with no more than two pigs per hectare. In these systems, males are castrated to avoid boar taint and females spayed to avoid the attraction and mounting by wild boars. The study was carried out in five different farms allocated in the south-west of Spain during two consecutive years, from March 2012 to February 2014, under the montanera regimen, and with a total of 995 animals observed (498 males and 497 females). The data were analysed with SAS by means of general models and proc mixed. Mean group size along the year was of 17±12.9 individuals, but this was significantly lower (P<0.05) during the montanera (12±0.8) and at midday (13±0.8). Groups were bigger (P < 0.05) when they were more than 50 m from a tree (23±1.8), or less than 10 m from the shelter (25±1.5), the feeding area (31±3.1) and the water-bath area (25±1.5). Nine percent of the groups were solitary animals, being higher (P=0.0286) during the montanera (11%) than the rest of the year (8%) and being formed in 68% by males. Males were less involved in mixed groups than were females (75% vs 91%), especially in spring, where the largest (P <0.0001) male groups were found. Female groups were less frequent and smaller (P <0.0001) than were male and mixed groups. In conclusion, although males were castrated at a very young age, they showed a different behaviour than females, forming in bachelor groups during the spring and being less involved in mixed groups and with more solitary animals. During the montanera, when animals were feeding on acorns and other natural resources, groups were smaller and closer to the trees, solitary males reaching a maximum percent.